MOLECULAR DOCKING ANALYSIS OF ACTIVE COMPOUNDS OF STAR FRUIT PLANTS WULUH (Averrhoa bilimbi. L) AGAINST NEPRILYSIN RECEPTORS AS ANTIHYPERTENSIVE DRUG CANDIDATES - Lindawati Setyaningrum; Mohamad Rofiq Usman; Asa Falahi; Anies Rohman Dwijayanti; Neny Poerwahyuningrum; Alwiya Kinanti (Indonesian Pharmacopeia Journal, 2026)
Hypertension is a major global health problem that significantly increases the risk of cardiovascular diseases. Neprilysin plays an essential role in blood pressure regulation and has emerged as a promising therapeutic target for antihypertensive drug development. This study aimed to evaluate the potential of active compounds from Averrhoa bilimbi L. as neprilysin inhibitors using an in silico approach. Molecular docking was performed between selected phytochemical compounds (Isocytisoside, Hallacton B, Vitexin 4″-O-rhamnoside, Epiafzelechin 3-O-gallate, and 2,4,6-Triphenyl-1-hexene) and the neprilysin receptor (PDB ID: 5JMY) using AutoDockTools. Docking protocol validation was conducted by redocking the native ligand, with validity determined by an RMSD value ≤ 3 Å. The grid box was set at coordinates x = −20.579, y = 3.317, z = 37.541 with dimensions of 40 × 40 × 40. Physicochemical properties and ADMET profiles were predicted using the pkCSM online server. The docking validation yielded an RMSD value of 1.303 Å, confirming the reliability of the docking protocol. Among the tested compounds, Hallacton B exhibited the most favorable binding affinity among the test ligands, with a binding energy of −9.45 kcal/mol and an inhibition constant (Ki) of 117.49 µM, along with key amino acid interactions comparable to the reference drug sacubitril. ADMET analysis indicated that Hallacton B possesses a favorable safety profile, showing negative results for Ames toxicity and hepatotoxicity, no inhibition of CYP2D6 and CYP3A4 enzymes, and acceptable distribution characteristics, although its intestinal absorption was relatively low (16.71%). Hallacton B demonstrates promising potential as a natural neprilysin inhibitor and warrants further optimization and experimental validation through in vitro and in vivo studies.